2008
DOI: 10.1209/0295-5075/84/50005
|View full text |Cite
|
Sign up to set email alerts
|

When are cellular automata random?

Abstract: A random cellular automaton is one in which a cell's behaviour is independent of its previous states. Analytical conditions for the existence of random cellular automata are derived and we find that a multitude of non-trivial random cellular automata exist. We develop an indicator variable formalism to further investigate these random automata and confirm analytical results with simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…This observation is in agreement with with the fact that while Wolfram highlighted some rule sets that produce randomness, most of his automata rules sets do not produce complex pseudo-random patterns [55]. Coe et al [68] analytically studied the question of when automata produce 'random' and complex dynamics, and also found that relatively few are random.…”
Section: Discussionsupporting
confidence: 79%
“…This observation is in agreement with with the fact that while Wolfram highlighted some rule sets that produce randomness, most of his automata rules sets do not produce complex pseudo-random patterns [55]. Coe et al [68] analytically studied the question of when automata produce 'random' and complex dynamics, and also found that relatively few are random.…”
Section: Discussionsupporting
confidence: 79%
“…, 254, 257; compare also Coe et al . ). This yields a probability for LE‐like growth that is equal to the (non‐trivial) proportion of R taken up by points that, when evolved forward by means of the (deterministic) dynamics concerning evolution through scriptS, yield LE‐like growth.…”
Section: Derivation Of Probabilistic Approximations To Deterministic mentioning
confidence: 97%